2012
DOI: 10.4103/0970-0218.103469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impairment and Disability on Health-Related Quality of Life of Elderly: A Community-Based Study from Urban India

Abstract: Introduction:Increasing population of elderly and the emergence of epidemic of chronic or (non-communicable) diseases, which is likely to adversely affects their health-related quality of life (HRQOL), has implications on health systems in developing countries such as India. A study was conducted to know the common impairments and disabilities and their effect on HRQOL in elderly population.Materials and Methods:A community-based cross-sectional study on elderly, selected by cluster sampling from central Delhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 4 publications
7
14
0
Order By: Relevance
“…Most of the HIV positive respondents on ART in this study were females. Our results confirm those of previous studies that have shown that the HIV/AIDS epidemic in South Africa is characterized by gender inequalities and that almost sixty percent of these infections occur in women (Robberstad and Olsen 2010;Lahariya et al 2012).…”
Section: Discussionsupporting
confidence: 95%
“…Most of the HIV positive respondents on ART in this study were females. Our results confirm those of previous studies that have shown that the HIV/AIDS epidemic in South Africa is characterized by gender inequalities and that almost sixty percent of these infections occur in women (Robberstad and Olsen 2010;Lahariya et al 2012).…”
Section: Discussionsupporting
confidence: 95%
“…Similar findings are present in a study conducted by Lahariya et al, where about 48.5% subjects had some form of impairment and only about 28.5% subjects had no disability or impairment. 5 Also, as the age advanced the percentage of individuals with impairment or disability increased which is similar to the trend observed by Lahariya et al, in his study. 5 This may be attributed to the fact that the elderly suffer from chronic diseases as the age advances.…”
Section: Discussionsupporting
confidence: 89%
“…The gender distribution in our study is almost similar to that reported by Lahariya et al, where about 44.5% of subjects were males and 55.5% of subjects were females. 5 Females have more life expectancy hence they tend to outnumber the male geriatric participants. Almost more than half of the respondents who were interviewed were from three generation families (51.46%), while 42.69% were from nuclear family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of hearing, vision, mobility, and increased risk of non-communicable diseases will appear along with the aging process [3] [4]. The mobility function plays an important role in the healthy aging, closely related to the quality of life of the elderly [5].…”
Section: Introductionmentioning
confidence: 99%